2021
DOI: 10.1186/s13018-021-02388-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of computed tomography-assisted limited decompression in the surgical management of thoracolumbar fractures with neurological deficit

Abstract: Objective To investigate the effect of CT-assisted limited decompression in managing single segment A3 lumbar burst fracture. Method A retrospective study (January 2015–June, 2019). One hundred six cases with single-level Magerl type A3 lumbar burst fractures treated with short-segment posterior internal fixation and limited decompression. Patients were divided into two groups: CT-assisted group and non-CT-assisted group. Perioperative factors, cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The effect of hypoxia on different subtypes is inherently heterogeneous. Nakamura et al found that pretreatment anemia was not associated with the prognosis of liposarcoma, while malignant fibrous histiocytoma was the opposite [23,42] . Patients may differ from study to study, so heterogeneity is acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of hypoxia on different subtypes is inherently heterogeneous. Nakamura et al found that pretreatment anemia was not associated with the prognosis of liposarcoma, while malignant fibrous histiocytoma was the opposite [23,42] . Patients may differ from study to study, so heterogeneity is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al found that pretreatment anemia was not associated with the prognosis of liposarcoma, while malignant fibrous histiocytoma was the opposite. [23,42] Patients may differ from study to study, so heterogeneity is acceptable. Second, the cutoff values between different studies are different.…”
Section: Survival Analysismentioning
confidence: 99%